Nanofluids heat transfer enhancement through straight channel under turbulent flow - Abdolbaqi, M. K. (Universiti Malaysia Pahang, 2015)
The need for high thermal performance thermal systems has been eventuated by finding different ways to enhance heat transfer rates. This paper introduces and analyzes numerically the heat transfer enhancement of nanofluids with different volume concentrations under turbulent flow through a straight channel with a constant heat flux condition. Solid nanoparticles of TiO2 and CuO were suspended in water as a base fluid to prepare the nanofluids. CFD analysis is conducted by FLUENT software using the finite volume method. The heat flux considered is 5000 W/m2, the Reynolds numbers are 104-106 with a constant volume concentration of 1-3%. Based on the analysis of the numerical results, it is found that the heat transfer rates and wall shear stress increase with increase of the nanofluid volume concentration. It appears that the CuO nanofluid significantly enhances the heat transfer. Furthermore, the numerical results are validated with the literature data available and show good agreement, with 4% deviation. The study concluded that the enhancement of the friction factor and Nusselt number is by 2% and 21%, respectively for the nanofluids at all Reynolds numbers. Therefore, nanofluids are considered to have great potential for heat transfer enhancement and are applied in heat transfer processes.